Comparative analysis of extraperitoneal versus transabdominal cesarean sections: a meta-analysis of randomized controlled trials and systematic review - Mengmeng Jia; Guangquan Ji; Ruifang Wang; Zhen Yan; Wei Niu; Jian Chen; Juanjuan Yu (BMC Surgery)
Abstract Objective The objective of this study is to systematically evaluate the efficacy of Extraperitoneal Cesarean Section (ECS) compared to Transabdominal Cesarean Section (TCS) in pregnant women, and to assess the differences in treatment outcomes between the two surgical approaches. Approach and techniques We conducted an extensive literature search, pulling up the most recent findings from reputable sources like the Cochrane Library, PubMed, EMBASE, Google Scholar, and Web of Science, all the way up to October 2024. Our meta-analysis comprised seven randomized controlled trials. We followed a fixed-effects model for results with less heterogeneity and a random-effects model for those with more. We utilized Stata 18 to conduct data analysis. For continuous data, we computed weighted mean differences (WMD). For categorical data, we calculated odds ratios (OR). We also included 95% confidence intervals (CI) with all of our results. We also used the Cochrane Risk of Bias tool to check all of the randomized controlled trials (RCTs) for bias. Results This meta-analysis did not find any statistically significant differences between the two groups when it came to baseline factors such as Body Mass Index (BMI), gestational week, and history of cesarean section. Statistical analysis revealed no significant differences in surgical outcomes (i.e., time to delivery(WMD 2.25, 95% CI -0.29 to 4.79, p = 0.083), time to operation (WMD 3.11, 95% CI -2.96 to 9.18, p = 0.316), neonatal weight (WMD -62.25, 95% CI -152.37 to 27.87, p = 0.176), 1-min Apgar score (WMD 0.03, 95% CI -0.39 to 0.45, p = 0.897), 5-min Apgar score (WMD 0.09, 95% CI -0.07 to 0.24, p = 0.296), blood loss (WMD 36.41, 95% CI -21.51 to 94.32, p = 0.218), etc.) between the TCS and ECS groups. However, the ECS group had a significantly shorter hospital stay (WMD -0.51, 95% CI -0.89 to -0.13, p=0.009) and less reduction in hemoglobin level (WMD -0.23, 95% CI -0.39 to -0.07, p=0.004) compared to TCS. Conclusion To sum up, this meta-analysis shows that ECS may help with postoperative hemoglobin level changes and shortening hospital stays. ECS may improve recovery metrics without adversely affecting maternal or neonatal outcomes. This analysis provides valuable insights that can guide clinical decision-making, even though there was no statistically significant difference between the two surgical approaches in terms of delivery time, operative time, neonatal weight, Apgar scores, or blood loss.